Policing health regulations in democratic societies: A focus on COVID-19 challenges and opportunities in Australia - Mazerolle, Lorraine (International journal of comparative and applied criminal justice, 2021)
Bayley stated just four short years ago that “… policing has become dramatically more complex in six ways: its tasks, public demands, strategies, technology, accountability and resources” (p. 164). The COVID-19 pandemic has clearly escalated these policing complexities creating a range of new responsibilities, tasks and strategies for police as well as raising new accountability questions. In this paper, we examine a number of new health regulations that are now commonplace for police to enforce including: restrictions on the number of people visiting private homes, maintaining physical distancing between people in public space, and mandated wearing of masks. We explore what these new tasks, public demands, and strategies mean for the future of policing in democratic societies. We conclude that the pandemic has created unprecedented access for police into the private lives of citizens creating what David H. Bayley would have seen as both as an opportunity and threat to civil society.